2009
DOI: 10.1038/jid.2009.39
|View full text |Cite
|
Sign up to set email alerts
|

N-Propionyl-Cysteaminylphenol-Magnetite Conjugate (NPrCAP/M) Is a Nanoparticle for the Targeted Growth Suppression of Melanoma Cells

Abstract: A magnetite nanoparticle, NPrCAP/M, was produced for intracellular hyperthermia treatment of melanoma by conjugating N-propionyl-cysteaminylphenol (NPrCAP) with magnetite and used for the study of selective targeting and degradation of melanoma cells. NPrCAP/M, like NPrCAP, was integrated as a substrate in the oxidative reaction by mushroom tyrosinase. Melanoma, but not non-melanoma, cells incorporated larger amounts of iron than magnetite from NPrCAP/M. When mice bearing a B16F1 melanoma and a lymphoma on opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 25 publications
(26 reference statements)
0
37
0
Order By: Relevance
“…Tumor-infiltrating T lymphocytes such as CD8 + and CD4 + T cells were observed both right and left tumors and tumorspecific cytotoxic T-lymphocyte (CTL) activity was augmented in the rats treated with MNHT. Jimbow et al also reported the anti-tumor immune responses induced by MNHT in mouse B16 melanoma models [22,23]. Thus, MNHT can kill not only heated tumors, but also non-heated tumors, including metastatic cancer cells.…”
Section: Induction Of Antitumor Immunity By Mnhtmentioning
confidence: 90%
See 2 more Smart Citations
“…Tumor-infiltrating T lymphocytes such as CD8 + and CD4 + T cells were observed both right and left tumors and tumorspecific cytotoxic T-lymphocyte (CTL) activity was augmented in the rats treated with MNHT. Jimbow et al also reported the anti-tumor immune responses induced by MNHT in mouse B16 melanoma models [22,23]. Thus, MNHT can kill not only heated tumors, but also non-heated tumors, including metastatic cancer cells.…”
Section: Induction Of Antitumor Immunity By Mnhtmentioning
confidence: 90%
“…The mice received daily intraperitoneal administration of NPrCAP/M. On the 15th day after injection of tumor cells, black brown MNPs were observed in B16F1 tumors whereas no substantial accumulation of the MNPs was observed in EG7 non-melanoma tumors [23].…”
Section: Magnetic Nanoparticles For Mnhtmentioning
confidence: 99%
See 1 more Smart Citation
“…95 Electron microscopy demonstrated this particle appeared only in melanoma cells. It was shown that the melanoma cells were degraded after the application of an external alternating magnetic field to increase the temperature in the tumor to 43°C.…”
Section: Magnetite Nanoparticlesmentioning
confidence: 99%
“…Thus, nanodrugs, once having entered the biological system, complexly interact with the host' s immune system, leading to premature clearance, side-effect activation, and toxicity (131)(132)(133)(134)(135). Consequently, the main limitations of nanodrug efficacy are the immunological interactions, the biological barriers that hinder the availability of nanodrugs to the intended target, and the heterogeneity of the biological target (38,136).…”
Section: Current Limitations and Exploring Possibilities For Improvinmentioning
confidence: 99%